RANCANG BANGUN SISTEM INFORMASI TUGAS AKHIR MENGGUNAKAN METODE WATERFALL DI FAKULTAS TEKNIK UNIVERSITAS ISLAM NUSANTARA - Yenni Fatman; Ipon Sarif Hidayat; Nisrina Ika Anadhiya (STKIP PGRI Situbondo, 2024)
One of the graduation requirements to get a bachelor's degree is to complete the final project. The implementation of the final assignment consists of several stages, starting with the submission of the proposal, proposal presentations, final project guidance, final project presentations, and final project defense. The Faculty of Engineering (FTEK) is one of the faculties at the Nusantara Islamic University (UNINUS). The implementation of the final assignment at FTEK UNINUS has not been well integrated because it still uses several different tools at each stage, making proposal seminar schedules, final project presentation schedules, and final project defense schedules is also still done manually by education staff (tendik). One of the ways to integrate the implementation of the final project is through information system development. Therefore, a website-based final project information system application was developed using the waterfall software development method with UML, the JavaScript programming language using the NextJS framework, and the PostgreSQL database. The result of this study is the final project information system website application, which is expected to help related parties at FTEK UNINUS implement their final project step by step